First test-beam results obtained with IDEA: a detector concept designed for future lepton colliders - Aly, Ramy; Antonello, M.; Azzi, P.; Bedeschi, F.; Bencivenni, G.; Borgonovi, L.; Caccia, M. L. M.; Chu, X.; Cibinetto, G.; Coates, T.; Cussans, D.; De Filippis, N.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2020)
IDEA (Innovative Detector for Electron-positron Accelerators) is a detector concept designed for a future leptonic collider operating as a Higgs factory. It is based on innovative detector technologies developed over years of R&D. In September 2018, prototypes of the proposed sub-detectors have been tested for the first time on a beam line at CERN. The preliminary results from this test of a full slice of the IDEA detector and standalone measurements of dual read-out calorimeter prototypes are presented.